A WS2 Case Theoretical Study: Hydrogen Storage Performance Improved by Phase Altering - Zhou, Jing; Cao, Jiamu; Shi, Jianing; Zhang, Yufeng; Chen, Junyu; Wang, Weiqi; Liu, Xiaowei (Nanoscale research letters, 2020)
Hydrogen is a clean energy with high efficiency, while the storage and transport problems still prevent its extensive use. Because of the large specific surface area and unique electronic structure, two-dimensional materials have great potential in hydrogen storage. Particularly, monolayer 2H-WS 2 has been proven to be suitable for hydrogen storage. But there are few studies concerning the other two phases of WS 2 (1T, 1T′) in hydrogen storage. Here, we carried out first-principle calculations to investigate the hydrogen adsorption behaviors of all the three phases of WS 2 . Multiple hydrogen adsorption studies also evaluate the hydrogen storage abilities of these materials. Comprehensive analysis results show that the 1T′-WS 2 has better hydrogen storage performance than the 2H-WS 2 , which means phase engineering could be an effective way to improve hydrogen storage performance. This paper provides a reference for the further study of hydrogen storage in two-dimensional materials.